Safety of infliximab and adalimumab in pediatric inflammatory bowel diseases: a disproportionality analysis from the FAERS database - Yanhong Deng; Shengying Shi; Senling Feng; Xiangping Tan; Yinling Wang; Jinjin Yin; Shaozhi Liu; Yuanmei Gao (BMC Gastroenterology)
Abstract Background The incidence of pediatric inflammatory bowel disease (IBD) significantly increased recently. Infliximab (IFX) and adalimumab (ADA), both TNF-α inhibitors, are the only FDA-approved treatments for pediatric IBD. Due to the unique physiological and developmental characteristics of children, postmarketing pharmacovigilance requires ongoing attention. We aimed to evaluate the safety of IFX and ADA in pediatric IBD using FAERS database data from Q1 2004 to Q1 2024. Methods Reporting Odds Ratio (ROR) and Proportional Reporting Ratio (PRR) algorithms were used to identify drug-related adverse events (AEs). Results In total, we retrieved 10,905 IFX-related reports and 5,446 ADA-related reports in pediatric IBD. Common AEs associated with IFX were infusion reactions; for ADA, they were injection site reactions. While most AEs align with approved labeling, continued vigilant monitoring appears important for specific postmarketing AEs observed with IFX, including suicide attempts, weight increased, and psoriasis. The median onset (TTO) for IFX-related AEs was 579 days (interquartile range [IQR]: 159.25–1357 days), occurring mostly after 360 days. For ADA, TTO was 79 days (IQR: 21.75–295 days), with most within 90 days of treatment initiation. Conclusion Our study revealed that although most AEs matched labeled information, rigorous post-marketing monitoring of severe AEs remains important for IFX and ADA in pediatric IBD, with additional confirmatory research warranted.